Distributed transient response modeling of rainfall-triggered shallow landslide for susceptibility assessment in Ribeira Quente valley (S. Miguel Island, Azores) - Amaral, P. (2019)
​In the last 15 years, several heavy rainstorms have occurred in Povoação County (S. Miguel Island, Azores), namely in Ribeira Quente Valley. These rainfall events have triggered hundreds of shallow landslides that killed tens of people and have been responsible for direct and indirect damages amounting to tens of millions of Euros. On the 6th March 2005 an intense rainfall episode, up to 160 mm of rain in less than 24 h, triggered several shallow landslides and caused 3 victims and damaged/blocked roads.